Análisis jurídico artículo 603 del Código Civil sobre el modo de adquirir el dominio por sentencia ejecutoriada de extinción de dominio en el Ecuador - Franco Peñafiel, José Sebastián (2024)
The present investigation was carried out with the objective of analyzing the reform of Article 603 of the 'Ecuadorian Civil Code', to determine the effects and scope of 'The Executory Judgment of Extinction of Ownership' as a new way of acquiring the domain, and to evaluate if the legal community knows this new civil institution\; for them the data collection was used in a direct way based on a documentary review of certain Civil preceptsand on the Law of Extinction of Ownership, likewise applying surveys to observe the knowledge of the legal society about this and its practical procedure. It was possible to understand that it is a subject with a lack of study, therefore, it was intended to generate knowledge about its effects and its title of acquisition of dominion, and it was resolved thatits normative introduction had certain formal inconsistencies